Insect Management for Onions, Leek, and Garlic - Susan E. Webb (EDIS)
This document is ENY-467 (which replaces ENY-435), one of a series of the Entomology & Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: August 2002.